Tourism, recreation and biological invasions
"This book provides a detailed review on the role of tourism and recreation in promoting biological invasions, and how invasions may affect these activities. It reviews management options and solutions to minimize the impacts from invasive non-native species in relation to tourism. It covers diverse regions and varied invasive organisms." --